Validity of a dietary calcium questionnaire modified to include supplement use in athletes - Henry, M. B.; Almstedt, H. C. (Journal of Sports Science & Medicine, 2009)
When conducting research in the area of bone health, accurate measurement of calcium intake is crucial. The rapid assessment method (RAM) is one technique that has frequently been used for its measurement of calcium intake. However, the RAM and other currently established questionnaires lack the assessment of dietary supplement use, which is common for athletes. Our objective was to evaluate the validity of a RAM questionnaire designed to assess daily calcium consumption which was further modified to meet the needs of athletes who frequently consume dietary supplements. Usefulness of the modified RAM for athletes and non-athletes was evaluated as well as utility among those who do and do not use supplements. The 47 volunteers (n = 31 women, 16 men) were between the ages of 18 and 25 including, 33 athletes and 14 controls. The population also contained 23 supplement users and 24 non-supplement users. Participants completed the modified RAM and were instructed to complete a three-day diet record (3DR), logging food intake for 2 weekdays and 1 weekend day. The data collected via the modified RAM was compared with the 3DR. Mean calcium intake was 935mg ± 420mg and 1085mg ± 573mg, for the modified RAM and 3DR respectively. A strong positive correlation (r) was found between calcium intake measured with the modified RAM and 3DRs (r(45) = 0.854, p < 0.01). Intraclass correlation coefficients (ICC) revealed that agreement between the two instruments was good (ICC = 0.76, df = 45, p < 0.01) and much improved when compared to agreements without consideration of supplements (ICC = 0.05, df = 21, p > 0.05). We have found the modified RAM to be a valid tool which can be used to estimate calcium intake in the athletes and controls we strive to study. The accuracy of this instrument improved by including assessment of dietary supplement sources of calcium.